2002
DOI: 10.1523/jneurosci.22-21-09430.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity Regulates Correlated Network Properties of Spontaneous Calcium Transients in AstrocytesIn Situ

Abstract: Spontaneous neuronal activity is essential to neural development. Until recently, neurons were believed to be the only excitable cells to display spontaneous activity. However, cultured astrocytes and, more recently, astrocytes in situ are now known to exhibit spontaneous Ca 2ϩ transients. Here we used Ca 2ϩ imaging of astrocytes from transgenic mice for the simultaneous monitoring of [Ca 2ϩ ] i changes in large numbers of astrocytes. We found that spontaneous activity is a common property of most brain astro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
209
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(226 citation statements)
references
References 79 publications
13
209
3
1
Order By: Relevance
“…This loading of fluo-4 and other calcium fluorescent dyes selectively into astrocytes in brain slices has been reported extensively (8,9,18,30), but its mechanism is not yet clear. It is possible that astrocytes may also be preferentially loaded with NP-EGTA under these conditions.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This loading of fluo-4 and other calcium fluorescent dyes selectively into astrocytes in brain slices has been reported extensively (8,9,18,30), but its mechanism is not yet clear. It is possible that astrocytes may also be preferentially loaded with NP-EGTA under these conditions.…”
Section: Resultsmentioning
confidence: 90%
“…During the past decade, it has become increasingly clear that they actively participate in intercellular communication in the brain (1)(2)(3). They are endowed with a variety of ion channels and receptors (4)(5)(6), and they display a form of excitability by changing the intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) (1)(2)(3)(7)(8)(9). Both application of neurotransmitters (1,5,10,11) and electrical stimulation of neuronal pathways (12,13) increase [Ca 2ϩ ] i in astrocytes.…”
mentioning
confidence: 99%
“…Astrocytes, the predominant type of glial cells in the central nervous system, form a highly organized multicellular syncytium extending throughout the gray matter (3,4). Calcium imaging in acute brain slices and in vivo has demonstrated that astrocytes can generate various patterns of activity, either local and spatially restricted to processes of individual cells or coordinated between adjacent cells and propagating across the brain tissue (5)(6)(7)(8)(9)(10)(11)(12). Modeling indicates that coupling of astrocytic and neuronal activities may give rise to membrane potential instability and oscillations (13).…”
mentioning
confidence: 99%
“…Since astrocytes do not require neuronal activity for Ca 2+ oscillations to occur, as has been shown in astrocytic cultures (Bowser and Khakh, 2007) or in slices (Aguado et al, 2002), one might speculate that astrocytic Ca 2+ waves, which are known to provoke ATP release, could potentially contribute to the adenosine release detected on sensors. Indeed, we could detect the release of ATP in response to DHPG, which was corroborated by an increase in phosphate production as measured by the malachite green phosphate assay, and an increase in the ATP sensor signal in response to the ecto-ATPase inhibitor ARL 67156.…”
Section: Purine Release During Mglur-dependent Oscillationsmentioning
confidence: 96%